Two new species of Mediomastus (Annelida, Capitellidae) from Tokyo Bay, Japan - Tomioka, Shinri; Nishi, Eijiroh; Kajihara, Hiroshi (Zookeys, 2014)
Two undescribed species of polychaetes in Mediomastus (Annelida: Capitellidae) were collected from intertidal to shallow habitats in Tokyo Bay, Japan. These are M. duobalteus sp. n. and M. hanedaensis sp. n. Mediomastus duobalteus sp. n. is distinguishable from all congeners by the following characters: 1) segments 3, 4, 8-11 stainable with methyl green, 2) thoracic capillary chaetae unilimbate, 3) abdominal capillary chaetae absent, 4) paddle-like chaetae in the thorax absent, and 5) abdominal hooded hooks not flared. Mediomastus hanedaensis sp. n. is similar to M. warrenae Green, 2002, but differs from the latter in the shapes of the thoracic capillary chaetae and the abdominal hooded hooks, and the staining pattern with methyl green. In addition, a key to all Mediomastus species is provided.
World Polychaeta Database (WPolyDb)